Studying of Phytochemical, Nutritive values and Antioxidant ability of Commiphora myrrha - Othman Rashid AL-Samarrai (College of Pharmacy / Mustansiriyah University, 2018)
The present study deals with the phytochemical, nutritional, mineral contents and in vitro antioxidant activity of Commiphora myrrha. Preliminary phytochemical result indicate that the plant contain phenolic compounds, flavonoids, tannins, glycosides, alkaloids, terpenoids and quinines. Secondary Metabolites has been estimate quantitatively, the highest concentration of tannins 3677.1 ±2.15 mg/100g and then for alkaloids 1880 mg/100g, sterols 155.215 ±1.00 mg/100g, and Flavonoids 47.266 ±0.013 mg/100g and phenolic compounds 30.647 ±2.481 mg/100g. Nutritional Profiling, minerals and antioxidant activity were determined. Flavonoids and glycosides isolated were exhibited lower reducing power and scavenging ability than ascorbic acid